A Guide to Tracking Physical Activity - Madison K. Keesling; Anne E. Mathews (EDIS)
Being physically active is fun, has many physical and mental health benefits, and can help maintain a healthy weight. The Physical Activity Guidelines for Americans recommend that adults be purposefully active for at least 150 minutes per week for overall health and wellness. One proven strategy to make sure you reach your activity goal is to track your energy expenditure. This 3-page fact sheet explains the different free and low-cost cell phone apps, websites, and portable devices available for tracking physical activity. Written by Madison K. Keesling and Anne E. Mathews, and published by the Food Science and Human Nutrition Department, August 2016.